E.03 Use of intra-arterial milrinone rescue therapy in patients with refractory and super refractory vasospasm after aneurysmal subarachnoid hemorrhage. (17th June 2016) - Alamri, AS; Alturki, A; Tampeiri, D; Angle, M; Lo, B; Lannes, M; Badawy, M; Teitelbaum, J
Abstract : Background: Vasospasm causing delayed ischemic neurologic deficit (DIND) remains a leading cause of devastating outcome after aneurysmal subarachnoid hemorrhage (aSAH). Therapy using intravenous milrinone (IVM) and intra-arterial milrinone (IAM) has been described. We report our results using IAM in patients with refractory and super refractory vasospasm (RV and SRV respectively).Methods: Retrospective single center study of all adult patients treated with IAM between 2006 and 2016 inclusively. IAM was used as part of the Montreal Neurological Hospital Protocol when the patients' symptoms failed to respond to initial and higher IVM doses. We report their clinical outcomes.Results: IAM was used in 19 patients. The median loading dose was 8 mg and average maintenance dose was 0.78 mcg/kg/min. Angiographic improvement was seen in 15 (79%) and clinical improvement - within the first 48 hours - was seen in all patients. The median mRS was 3 at time of discharge and 1 three months later. Five patients lost follow up.Conclusions: IAM appears to be safe and effective in this small retrospective series of RV and SRV complicating aSAH. Angiographic and clinical improvements were observed. Further prospective studies are warranted to confirm these findings.